2007
DOI: 10.1016/j.fusengdes.2007.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Infrared images data merging for plasma-facing component inspection

Abstract: The data merging study of the two infrared thermography non-destructive techniques on W7-X divertor targets allowed to improve significantly the sensitivity and reliability of detecting the fault size and location at the tile interfaces. This was possible due to the merging of infrared images. This original method of tile interfaces inspection has been validated using calibrated defects and then applied on fabricated components. The data merging method of infrared thermal images using the fuzzy logic method an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Beside the data post-processing in terms of DTref max parameter, others advanced infrared image and data post-processing were studied and combined to handle information from SATIR by another way to obtain a more reliable results minimizing the global uncertainty. A data merging method [5] was chosen to process by combining information arising from different data-processing for a same source (i.e. thermo-signal SATIR).…”
Section: Upgraded Acceptance Criterionmentioning
confidence: 99%
“…Beside the data post-processing in terms of DTref max parameter, others advanced infrared image and data post-processing were studied and combined to handle information from SATIR by another way to obtain a more reliable results minimizing the global uncertainty. A data merging method [5] was chosen to process by combining information arising from different data-processing for a same source (i.e. thermo-signal SATIR).…”
Section: Upgraded Acceptance Criterionmentioning
confidence: 99%
“…This original study, using fuzzy logic through a Dempster-Shafer model, showed detection improvement of LOCKIN and SATIR methods (figure 11). The data merging method is now in operation at CEA [13]. From the experimental know-how gained during the development of each individual NDE method, it will be possible to implement a data merging process with moderately reduced training.…”
Section: Data Mergingmentioning
confidence: 99%
“…The principle is the detection of a delay in the surface temperature evolution introduced by an abrupt variation of the temperature of the water flowing in the cooling channel, which is compared to the response of a reference "defect-free" element. The reliability in the interpretation of the results of NDEs is being improved by the data merging method [13]. These approaches have limitations because they provide an acceptance criterion to characterize only the thermal and not the mechanical performance of the bond.…”
Section: Acceptance Criteriamentioning
confidence: 99%